Penerapan Metode Murojaah dalam Meningkatkan Hafalan Asmaul Husna di SDN Kramatjegu 1 Taman Sidoarjo - Lailatus Shamadiyah; Abdullah Abbas Fattah; Nelud Darajatul Aliyah (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
In the era of Gen Z, many children are reluctant to know about religion. Every time you get a memorization task, it is always not in accordance with the time specified for deposit. And do not feel burdened or eager to be able to memorize in order to get additional grades. But they are more likely to prefer playing online games to fill their free time at home rather than taking a break to take a nap after school. The focus of service in this mentoring is assistance in improving memorization with the murojaah method. This service uses the Participatory Action Research method where the author is actively involved in direct service activities. Service activities related to memorizing asmaul husna with the murojaah method can strengthen cooperation with peers and get rewards.